FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN POSYANDU LANSIA DI KELURAHAN BULUSAN, KECAMATAN TEMBALANG, KOTA SEMARANG - Hana Maulida Muflikhah; Bagoes Widjanarko; Anung Sugihantono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Based on the data from the Central Statistics Agency (BPS) in Central Java showed the number of elderly in the district Tembalang in 2014 as many as 5,273 people. The increase in the number of elderly in the world to make a new problem of healthy. Therefore, the government issued the Law number 36 Year 2009 on Health, article 138 states that the efforts of health care for the elderly must be shown to maintain in order to stay healthy and productive life socially and economically appropriate human dignity. Therefore formed a Posyandu efforts to realize the law. The purpose of this study was to determine the factors related to the utilization of Posyandu Elderly in Bulusan Village, District Tembalang, Semarang. The method used in this research is quantitative with cross sectional approach. Total population 37 participants Posyandu with a total of 37 samples were taken using a total sampling system. The Data were analyzed using univariate and bivariate analysis with statistical test Chi Square (significance level 0.05). The results showed no relationship between perception of disease severity (0,000), and Perceived Benefits (0,013) by utilization of Posyandu as p <0.05. While the perception of limitations respondents (.515) is not related to the utilization of Posyandu in Bulusan Village, District Tembalang, Semarang. Suggestions from this study is Implement monitoring and evaluation of the elderly Posyandu every month on the performance of health workers and health volunteers, increase understanding of the importance of the elderly Elderly Posyandu activities, and cooperation with the relevant parties to improve services in Posyandu.